Concerta ® para aprender: os impactos do discurso patologizante na educação - Flávia Luíza de Freitas Albuquerque (2021)
The study object of this thesis deals with a frequent phenomenon in school institutions in recent decades: the pathologizing discourse on school failure. Faced with this issue, we seek as a general objective to analyze how complaints regarding school failure have been produced in a public elementary school. To achieve this objective, semi-structured interviews were conducted with professionals from the Multiprofessional Sector of a Public Elementary School in the city of Belo Horizonte (Brazil), which is very similar to a psycho pedagogical clinic. Thus, we seek to answer: how do professionals in this Multidisciplinary Sector deal with complaints from teachers and students? Does the practice of these professionals reveal pathologizing biases? As theoretical-methodological assumptions used in the investigation of the meanings, attributed by professionals in the Multiprofessional Sector, to school failure, references of Historical-Cultural Psychology by L. S. Vygotsky and Ethnography in Education were used. The dialogue between Historical-Cultural Psychology and Ethnography in Education allowed us to withdraw from the carried out interviews the basic unit of analysis of this research [situated social cognition-affect-pathologization]. From the transcription of the interviews into message units, expressive cases were chosen in order to conduct the contrastive analysis between the discourses of the professionals in the Multiprofessional Sector. As a result, it was noticed that the trajectory of this sector was marked by a punishing and disciplinary logic towards the students at ABCD School. Thus, we conclude that the actions of these professionals are mostly individual and do reveal pathologizing biases. However, there are critical discourses of this practice among professionals in this sector. In view of the approval of Brazilian Federal Law No. 13.935/2019, we seek, with our research, to contribute to the reflection on how the work of these professionals who already work in the scholar environment has been developed with complaints about school failure and, in this way, build new paths to the professionals who will start their actions with the implementation of the law.